Computational nanotechnology : modeling and applications with MATLAB - Musa, Sarhan M Ed (Nano and energy series, 2011)
"Written to help professionals, researchers, and students discover the challenges and opportunities associated with development of next-generation nanoscale computational nanotechnology, this book covers a broad range of technical information, research ideas, and practical knowledge regarding applications in this area. Offering thought-provoking perspective on the developments that are poised to revolutionize the field, the author explores both existing and future nanotechnology applications, which hold great promise for significant innovations in engineering, physics, chemistry, biology, and medicine"--